O tratado de cooperação amazônica: áreas protegidas e regimes ambientais - Torquato , Carla Cristina Alves (2008)
This work deals with the analysis of Amazon protected areas and territorially protected areas of the countries belonging to the Amazon Basin, Brazil, Bolivia, Colombia, Ecuador, Peru and Venezuela, through the Amazon Cooperation Treaty, signed the pledge to promote development harmony in the region through cooperation and reciprocity of efforts for the region's economic growth coupled with environmental protection. From this premise, the contracting parties to the Treaty seek to make efforts and joint actions and deeds are one of the systems of protected areas territorially in these countries, which had the basic construction of the Convention of Biological Diversity - CBD and the guidelines system of protected areas the International Union of nature conservation - IUCN and the construction of the same and what role these two instruments within international law. This is analyzed similarities, opportunities for harmonization or unification between the systems, the phenomenon of legalization, the function of the CBD and the system of protected areas guidelines of IUCN as soft law instruments , training and environmental change of a regime and the attempt the state constitutional cooperative as germ of a wider cooperation KEY-WORDS : PROTECTED AREAS, INTERNATIONAL LAW, AMAZON COOPERATION TREATY , LEGALIZATION, SOFT LAW, INTERNATIONAL REGIMES.